Electrophysiological assessment of Chronic Inflammatory Demyelinating Peripheral Polyradiculoneuropathy(CIDP) in Patients with Diabetes Mellitus - Suhail, Marwa S.; Mohammed, Najeeb H.; Ali, Safaa H. (Journal of the Faculty of Medicine Baghdad, 2014)
Back ground: Peripheral neuropathy is a common complication of diabetes mellitus. However, patients with diabetes are more vulnerable to develop chronic inflammatory demyelinating peripheral polyradiculoneuropathy (CIDP) which is an acquired immune mediated disorder. Subjects and methods: Three groups of subjects of either sex involved in this study; fourty one (41) patients with diabetic CIDP, fourty six (46)patients with diabetic peripheral polyneuropathy and fourty one (41) control subjects. Sensory and motor nerve conduction study (NCS) and electromyography (EMG) of both upper and lower limbs were performed for each subjects. This study was conducted at the unit of neurophysiology in Neuroscience Hospital and Al- yarmouk Teaching Hospital, in a period from November /2012 to May /2013. Objectives: : Assess the role of electrophysiological study (NCS and EMG) in the diagnosis of CIDP in diabetic patients and Differentiate between diabetic CIDP and diabetic peripheral polyneuropathy(PNP). Results: Prolonged distal sensory latency distal (DSL), decreased sensory nerve action potential (SNAP) amplitude and slowing of sensory nerve conduction velocity (SNCV). Sensory NCS was significantly changed in both patients groups. While the presence of abnormal median-normal sural (AMNS) and abnormal radial – normal sural (ARNS) pattern of sensory involvement were detected only in diabetic CIDP patients. Concerning motor nerve conduction study, prolonged distal motor latency (DML), slowing of conduction velocity and prolonged mean F-wave latency were detected in both patients group, but these abnormalities were more in diabetic CIDP patients. Conduction block CB% and abnormal temporal dispersion TD% were observed only in diabetic patients with CIDP. Whereas needle EMG of diabetic CIDP revealed that there are mixed axonal and demyelinating neuropathy. Conclusion: This study conclude that the abnormal sensory and motor NCS in the lower limbs were higher when compare with that of upper limbs. However, the changes in motor parameters are more in diabetic patients with CIDP than that of diabetic PNP. In addition, the proximal nerve segments are more vulnerable to be affected by demyelinating process rather than the other segments. Moreover, most of diabetic patients with CIDP have mixed axonal and demyelinating changes in respect to those who had only demyelinating neuropathy.